"Coming out" rhetoric in disability studies: Exploring the limits of analogy by looking at its fit with the Deaf experience - Mauldin, Laura (Disability Studies Quarterly, 2018)
This article takes as its entry point the borrowing of coming out discourse in Disability Studies. It first discusses the limits of using such analogies and then investigates its fit when considering the specificity of the Deaf experience. The research is based on five personal histories garnered through in-depth interviews with individuals primarily discussing their processes of coming to identify as Deaf, but also some discussion of coming to identify as gay/lesbian. Their stories indicate that unlike its deployment in broader disability studies, the discourse of coming out in relation to adopting a Deaf cultural identity does not resonate. Instead, the narratives show that while these Deaf individuals did use a sign for "coming out" to describe their process of identifying as gay/lesbian, they did not use it to describe their Deaf identity development. Their narratives of coming to identify as culturally Deaf instead predominantly use a phrase that can interpreted from sign language as "becoming Deaf," although some of the same processes and features of identity development are present. It concludes with a discussion of the tensions between Deaf and disability studies, the limits of analogizing disability with other categories and particularly the limits of coming out discourse regarding the Deaf experience, as well as a discussion of the universalizing view of disability studies.